Istota prawnokarnej ochrony obrotu gospodarczego - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the essence of economic trade criminal law protection. The author, basing on the catalog of offenses against economic trade provided under Chapter XXXVI of the Criminal Code indicates the important issue of defining economic trade as am object of criminal law protection.At the same time, the author indicates its close relation to the legal definition of economic activity provided by the Act of 2 July 2004 on freedom of economic activity. The author also refers to the current postulates aimed at increasing the effectiveness of the protection of financial interests of traders as well as new provisions concerning proper business transactions.
Keywords: prawo karne; ochrona prawnokarna; obrót gospodarczy